Why and when social support predicts older adults' pain-related disability: a longitudinal study - Matos, M. (2018)
Pain-related social support has been shown to be directly associated with pain-related disability, depending on whether it promotes functional autonomy or dependence. However, previous studies mostly relied on cross-sectional methods, precluding conclusions on the temporal relationship between pain-related social support and disability. Also, research on the behavioral and psychological processes that account for such a relationship is scarce. Therefore, this study aimed at investigating the following longitudinally: (1) direct effects of social support for functional autonomy/dependence on pain-related disability, (2) mediating role of physical functioning, pain-related self-efficacy, and fear, and (3) whether pain duration and pain intensity moderate such mediating processes. A total of 168 older adults (Mage = 78.3; SDage = 8.7) participated in a 3-month prospective design, with 3 moments of measurement, with a 6-week lag between them. Participants completed the Formal Social Support for Autonomy and Dependence in Pain Inventory, the Brief Pain Inventory, the 36-SF Health Survey, behavioral tasks from the Senior Fitness Test, the Pain Self-Efficacy Questionnaire, and the Tampa Scale for Kinesiophobia. Moderated mediation analyses showed that formal social support for functional dependence (T1) predicted an increase in pain-related disability (T3), that was mediated by self-reported physical functioning (T2) and by pain-related self-efficacy (T2) at short to moderate pain duration and at low to moderate pain intensity, but not at higher levels. Findings emphasized that social support for functional dependence is a risk factor for pain-related disability and uncovered the “why” and “when” of this relationship. Implications for the design of social support interventions aiming at promoting older adults' healthy aging despite chronic pain are drawn.